2013
DOI: 10.1080/10934529.2013.781884
|View full text |Cite
|
Sign up to set email alerts
|

Determination of selected phthalate esters compounds in water and sediments by capillary gas chromatography and flame ionization detector

Abstract: The presence of phthalate esters (PAEs) in the environment is not desirable and therefore, needs to be monitored. This study reports the first data on the concentration levels of PAEs in water and sediments of the Jukskei River catchment area, South Africa. The study was conducted during the summer and winter seasons of 2005. Liquid-liquid extraction (LLE) and Soxhlet extraction (SE) methods were optimized, evaluated and used to determine PAEs of interest in water (unfiltered and filtered) and sediments sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
15
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 35 publications
9
15
1
Order By: Relevance
“…The DnOP concentrations in the sediments of the present study are two orders of magnitude higher than those reported in other studies (Vitali et al, 1997;Vethaak et al, 2005;Zeng et al, 2008;Sun et al, 2013). The composition analysis indicates that DEHP was the most abundant congener in the southern Jiangsu suburban river sediments, which agrees with some previous studies (Tan, 1995;Sha et al, 2007;Sun et al, 2013;Chen et al, 2013;Sibali et al, 2013). However, extremely high concentrations of diisobutyl phthalate in Guangzhou City and DnBP in river sediments in Taiwan have also been recorded (Yuan et al, 2002;Zeng et al, 2008).…”
Section: Comparison With Other Studiessupporting
confidence: 87%
See 1 more Smart Citation
“…The DnOP concentrations in the sediments of the present study are two orders of magnitude higher than those reported in other studies (Vitali et al, 1997;Vethaak et al, 2005;Zeng et al, 2008;Sun et al, 2013). The composition analysis indicates that DEHP was the most abundant congener in the southern Jiangsu suburban river sediments, which agrees with some previous studies (Tan, 1995;Sha et al, 2007;Sun et al, 2013;Chen et al, 2013;Sibali et al, 2013). However, extremely high concentrations of diisobutyl phthalate in Guangzhou City and DnBP in river sediments in Taiwan have also been recorded (Yuan et al, 2002;Zeng et al, 2008).…”
Section: Comparison With Other Studiessupporting
confidence: 87%
“…The range of PAE concentrations found in sediments in other areas is shown in Table 2. The PAE concentrations in the river sediments of the present study are generally higher than those in other locations around the world (Tan, 1995;Vitali et al, 1997;Fromme et al, 2002;Vethaak et al, 2005;Adeniyi et al, 2011;Sibali et al, 2013). The concentrations of DMP and DEP are comparable among several studies and have been relatively stable, while the DnBP and DEHP concentrations in sediments vary dramatically among several studies (Vitali et al, 1997;Chou and Robert, 2006;Srivastava et al, 2010).…”
Section: Comparison With Other Studiessupporting
confidence: 48%
“…Similarly, a few studies (Adeniyi et al, 2008;Fatoki et al, 2010;Sibali et al, 2013) have determined the levels of phthalates in aquatic systems in South Africa. These compounds are used as additives in a wide range of polymeric materials (USEPA, 2012;Sun et al, 2016;Yang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…These compounds are used as additives in a wide range of polymeric materials (USEPA, 2012;Sun et al, 2016;Yang et al, 2019). Sibali et al (2013) found that the levels of phthalates ranged from 40 to 100 μg/L in water and 0.10 to 4,910 ng/g in sediment from the Juskei River catchment area (Gauteng Province). These concentrations were much lower than those determined by Fatoki et al (2010) in rivers and dams in the Venda region (Limpopo Province), where phthalate levels ranged from 160 to 10 200 μg/L and 20 to 890 ng/g in water and sediment, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Salt farmers generally try to remove some of the extractable pollutants from PVC by soaking the material in seawater for 4 to 6 months before salt production, and they use the PVC materials for 5 to 7 years. Despite efforts to remove pollutants from PVC, phthalate has been one of the most frequently detected environmental pollutants in water ( 16,17) because removal of all the extractable phthalate from PVC is difficult. Thus, phthalate contamination in salts is a major food safety concern in Korea.…”
mentioning
confidence: 99%